Robustness in production systems – findings from a systematic literature review. (9th March 2023) - Stockmann, Christian; Winkler, Herwig
In production systems, the concept of robustness is widespread due to various applications, purposes, and interpretations. However, little is known about the conceptual characteristics of robustness in production settings and even less about its distinctions from other related terms – such as flexibility or agility. That is why this paper systematically reviews production literature to identify the contexts in which robustness is mostly applied and to analyse existing concepts. It is found that despite a vast literature body addressing robustness in varying forms, few studies cover it on a conceptual basis. Within this small sample, a rather general agreement on the meaning of robustness in production systems is found. However, details, interpretations, mentioned interlinkages to related terms differ across the identified literature. Based on the findings of the review and with the help of established literature on adjacent concepts, a comprehensive understanding of robustness in production systems is developed.